Determinant Audit Report Lag in Indonesia Financial Industry: An Analysis Pre and During Covid-19 - Ghaisani, Firdina Intan; Kholid, Muamar Nur (Journal of Business & Banking, 2025)
Covid-19 has affected the economy and business environment, including the process of implementing company financial report audits. This study examines the determinants of audit report lag in the financial industry in Indonesia. Specifically, this study examines audit report lag by comparing the periods before and during the Covid-19 period. This study examines four independent variables related to audit characteristics and the company's financial condition. The population in this study were financial sector companies listed on the Indonesia Stock Exchange from 2017 to 2022. Forty-six companies in the Indonesian financial industry were selected as samples using purposive sampling techniques. The results of the data analysis showed that profitability and the size of the public accounting firm did not affect audit report lag either before or during the Covid-19 period. The analysis results also showed that audit fees affected audit report lag before and during the Covid-19 period. Meanwhile, audit tenure affected audit report lag only during the period before Covid-19